Δ(9)-Tetrahydrocannabinol acts as a partial agonist/antagonist in mice - Paronis, Carol A; Nikas, Spyros P; Shukla, Vidyanand G; Makriyannis, Alexandros (Behavioural pharmacology, 2012)
Δ-Tetrahydrocannabinol (THC) has been characterized as a partial agonist at cannabinoid CB1 receptors in vitro; however, it often produces the same maximum effects in vivo as other cannabinoid agonists. This study was carried out to determine whether THC would antagonize the hypothermic effects of another cannabinoid agonist, AM2389, in mice. Male mice were injected with 1-100 mg/kg THC, 0.01-0.1 mg/kg AM2389, or a combination of 30 mg/kg THC and 0.1-1.0 mg/kg AM2389, and rectal temperature was recorded for up to 12 h after injection. THC reduced the temperature by 5.6°C at a dose of 30 mg/kg; further increases in the dose did not produce larger effects, indicating a plateau in the THC dose-effect function. AM2389 reduced temperature by 9.0°C at a dose of 0.1 mg/kg. One hour pretreatment with 30 mg/kg THC attenuated the hypothermic effects of 0.1 mg/kg AM2389; a 10-fold higher dose, 1.0 mg/kg AM2389, was required to further decrease temperature, reflecting a five-fold rightward shift of the lower portion of the AM2389 dose-effect function following THC pretreatment. These results indicate that, in an assay of mouse hypothermia, THC exerts both agonist and antagonist effects following acute administration, and mark the first demonstration of partial agonist/antagonist effects of THC in vivo.